2014
DOI: 10.1166/jnn.2014.8828
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Patterning of Proteins on Wettability Gradient Surface by Thermo-Transfer Printing

Abstract: We develop a simple and biocompatible method of patterning proteins on a wettability gradient surface by thermo-transfer printing. The wettability gradient is produced on a poly(dimethylsiloxane) (PDMS)-modified glass substrate through the temperature gradient during thermo-transfer printing. The water contact angle on the PDMS-modified surface is found to gradually increase along the direction of the temperature gradient from a low to a high temperature region. Based on the wettability gradient, the gradual c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Studies have shown that the transferred PDMS results in a large variation in the contact angle. 29) Based on the results of the AFM images, the capacitance-voltage characteristics, current-voltage characteristics, and contact angles of the bare and SCC-processed ferroelectric insulators, it was found that the surface morphology was modulated by the SCC process without varying the ferroelectric dielectric property and surface energy.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the transferred PDMS results in a large variation in the contact angle. 29) Based on the results of the AFM images, the capacitance-voltage characteristics, current-voltage characteristics, and contact angles of the bare and SCC-processed ferroelectric insulators, it was found that the surface morphology was modulated by the SCC process without varying the ferroelectric dielectric property and surface energy.…”
Section: Resultsmentioning
confidence: 99%
“…In most previous works, the pattern roughness and the topographic mismatch across the hydrophobic and hydrophilic regions positioned underneath a supported lipid membrane were found to render lipid-free gaps 15 16 17 at monolayer-bilayer boundaries. In our case, the self-inking PDMS transfer 23 by thermally-assisted contact printing 24 25 ( Fig. 1B ) was employed to produce the MBJs with high spatial fidelity on a hydroxylated glass substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Due to reactions of the transferred oligomers with silanols on the glass surface 27 28 , the hydrophobic patterns exhibited the long-term stability over 30 days 24 . As shown in Table 1 , the contact angle ( θ c ) of water on the S-PDMS surface increases monotonically with the printing temperature, i.e., the surface energy decreases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation